The development of the Italian economy - CLARK, C. (PSL Quarterly Review, 2014)
The Central Institute of Statistics has recently calculated figures for the Italian national income - at factor cost and at market prices - going back as far as 1901. These data provide the basis for an estimate of productivity for Italy from 1901 to 1953. The present article summarises the results of this investigation. According to the author, it appears that since the Second World War the rate of growth of productivity in Italy has once more reached the figure of about 3.5 percent per year. This is the level which characterised the period 1901 to 1925, and must be classed amongst the highest rates of growth to be encountered anywhere in the world. JEL: E01, O11, O47, O52